A new approach to identifying the effect of diabetic peripheral neuropathy on the ability to drive safely. (February 2020) - Perazzolo, M.; Reeves, N.D.; Bowling, F.L.; Boulton, A.J.M.; Raffi, M.; Marple-Horvat, D.E.
Highlights: Diabetic peripheral neuropathy affects multiple aspects of driving performance. Drivers with neuropathy use the mid-range of the accelerator pedal much less. Use of the steering wheel, and eye-steering coordination are also both affected. Drivers with neuropathy occasionally experience difficulty controlling the vehicle. Driving with neuropathy improves when driving the same route a second time. Abstract: The purpose of this study was to estimate the potential for impaired driving performance in current drivers with diabetic peripheral neuropathy compared to healthy controls. We analysed, using a driving simulator, three important aspects of driving - use of the accelerator pedal, steering wheel and eye-steering coordination - to test for any differences, and then to integrate these findings to identify a unique pattern of changes in people driving with diabetic peripheral neuropathy. Patients with diabetic peripheral neuropathy displayed differences in use of the accelerator pedal compared to healthy control drivers (p < 0.05) which could be a direct consequence of their sensorimotor impairment due to diabetic peripheral neuropathy. Drivers with DPN used the more extreme high and low positions of the pedal to a greater extent than the Control group who exhibited a more graded use of the accelerator pedal over the mid-range. Eye-steering coordination was also different in drivers with diabetic peripheral neuropathy (p < 0.05) and, as it improved during the second drive, becoming closer to healthy drivers' values, the occasional loss of control experienced during driving reduced. These insights demonstrate that diabetic peripheral neuropathy affects multiple aspects of driving performance suggesting the need for an integrated approach to evaluate the potential for driving safely in this population.